Elevated lysine crotonylation and succinylation in the brains of BTBR mice. Issue 76 (August 2019) - Wang, Min; Chang, Qiaoqiao; Yang, Hua; Liu, Yongfeng; Wang, Chunfang; Hu, Fengyun; Wei, Hongen; Li, Rongshan
Highlights: We detected four novel PTMs level in the brain of BTBR mice. Crotonylation and succinylation are elevated in BTBR mice. A possible mechanism of crotonylation and succinylation involved in abnormal neuroanatomical structures in BTBR mice is proposed. Abstract: The BTBR T + Itpr3tf/J (BTBR) mouse has developmental disorders in the central nervous system and many aberrant neuroanatomical structures. However, identification of the pathological mechanisms underlying these abnormal neuroanatomical structures in the brains of BTBR mice is still lacking. Posttranslational modifications (PTMs) are known to be involved in the regulation of diverse cellular processes, and evidence shows that some types of PTMs are associated with the development of the central nervous system. In this study, we detected four novel PTMs in the cerebral cortex of BTBR mice as compared to C57BL/6 J (B6) mice using western blotting. Results revealed that lysine crotonylation and succinylation were elevated in the cerebral cortex of BTBR mice compared to levels in B6 mice. We speculate that elevated profiles of lysine crotonylation and succinylation may be involved in mechanisms related to neuroanatomical abnormalities in cerebral cortex of BTBR mice.